Properties of kenaf bast fibre cement composite board - Ahmed Basher, Amel Basher (2013)
Kenaf bast fibre (KBF) is rich in cellulose and, has high tensile strength, which is suitable for reinforcement of cement-bonded board. This study used kenaf bast fibre as partial replacement for cement as well as reinforcement for cement board. The work comprised the evaluation of mechanical and physical properties of kenaf bast fibre which were separated using different extraction methods (water, decortication and chemical), hydration behaviour, and the effects of different board formulations on the properties of cement-bonded kenaf board (CBKB). The objectives of the study were: 1) to evaluate the effects of fibre separation method on the physical, chemical and mechanical properties of kenaf bast fibre, 2) to determine the effect of incorporation of kenaf bast fibre, accelerators (calcium chloride (CaCl2), aluminium chloride (AlCl3), sodium sulfate (Na2SO4) and calcium oxide (CaO2)) and additives (silica fume and superplasticiser) on the hydration properties of Portland cement, 3) to evaluate the mechanical properties and dimensional stability of cement-bonded kenaf board, 4) to examine the curing behaviour of cement-bonded kenaf board, and 5) to characterize the permeability , surface and thermal behaviour of cement-bonded kenaf board. The performance of different CBKB densities was evaluated based on the strength – modulus of rupture (MOR), the stiffness – modulus of elasticity (MOE) and internal bonding (IB). The dimensional stability was assessed by determining the percentage of water absorption (WA) and thickness swelling (TS). The morphological properties of kenaf bast fibre were found to be significantly affected by the extraction methods used. Using sodium hydroxide (NaOH) for retting reduced the fibre lumen diameter and increased the cell wall thickness significantly. Both benzoate- and water-retted fibres experienced the same but at a much lesser effect. Mechanical decortication however was found to excessively reduce the cell wall thickness much thinner than the crude (unprocessed) fibre. There was a small increment in fibre density for NaOH-retted and benzoate-retted bast fibres over those of water, decorticated and crude (control). The densified fibre may be contributed by the amount of chemicals being absorbed into the fibre. Among the different extraction methods used, decorticated, water and NaOH-retted fibres have significantly higher tensile strengths. The hydration test suggests that NaOH and benzoate were not suitable for the kenaf retting. Both NaOH- and benzoate-retted fibres had relatively higher pH hydration time and low maximum hydration temperature which is not conducive for curing of cement-bonded kenaf board. Both water-retted and decorticated KBF had good hydration properties, and suitable for cement board production. The suitable fibre size is > 3.5 mm. Fibres with smaller size apparently require the addition of accelerators to enhance their compatibility. Among the different accelerators used, CaCl2, AlCl3, Na2SO4 and CaO, both CaCl2 and CaO proved to be the best with their optimal concentration at 2%. Between the two additives used, silica fumes (SF) and superplasticiser (SP), the former was found to be a better choice based on it is hydration properties. Among the methods of fibre separation, water retting and decortication produced fibres of good quality, high tensile strength, good hydration properties, good fibre morphology and high cellulose content. Incorporation of KBF in cement-bonded board generated reasonably light and strong panel, however, the IB was reduced significantly. The main reason for this is the separation of kenaf fibres from cement creating a weak inter-particle bonding within the board. Almost all the failures were observed to occur at the interface. Adding SF at 7% improved the IB by 83%. The presence of board density also has a negative effect on the mechanical properties and the dimensional stability of the boards. Among the three cement: KBF proportions (2:1, 2.5:1 and 3:1) used in this study,using 2:1 resulted in boards with the best performance in terms of MOR, MOE, WA and TS. The best combination to produce acceptable performance CBKB is by using decorticated KBF, at 2:1 (cement: KBF), 7% SF and board density (1100 kg/m3). The properties: MOR (10.9 MPa), MOE (5061 MPa), IB (0.15 MPa), WA after 2h and 24h (23.7 and 27%, respectively), TS after 2 and 24h (0.87 and 3.01%,respectively.